(3VQGFH GdONd hGdKQhI hGdCfaGb aj dHfGfs - (3GdeQSj(B, (3GdSjO MLGRjs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3VQGFH GdONd , GdVQjHI Ydi GdCQHGM GdUfGYjI hGdJLGQjI hZjQ GdJLGQjI , GdVQjHI Ydi GdQhGJH hGdCLhQ heYGTGJ GdJbGYO , GdVQjHI Ydi ONd QDhS GdCehGd GdefbhdI , VQjHI GdCQGVj , VQjHI GdCedGc GdeHfjI , VQGFH GdKQhI , GdQSe hGdEfJbGd VQGFH GdEfaGb , GdVQGFH GdLeQcjI , QSe GdWGHY GdeGdjs
Keywords: (3VQGFH GdONd (B- (3dHfGfs